2017
DOI: 10.1152/japplphysiol.00834.2016
|View full text |Cite
|
Sign up to set email alerts
|

Transspinal direct current stimulation modulates migration and proliferation of adult newly born spinal cells in mice

Abstract: Direct current electrical fields have been shown to be a major factor in the regulation of cell proliferation, differentiation, migration, and survival, as well as in the maturation of dividing cells during development. During adulthood, spinal cord cells are continuously produced in both animals and humans, and they hold great potential for neural restoration following spinal cord injury. While the effects of direct current electrical fields on adult-born spinal cells cultured ex vivo have recently been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 74 publications
2
11
0
Order By: Relevance
“…Hence, a given electrical field polarity can increase spinal tract excitability in the white matter and simultaneously decrease excitability in neural elements in the gray matter, or vice versa. There is some pioneering work exploring the effects of tsDCS in animals (Fuortes, 1954), showing the potential of this technique in modulating spinal circuitry (Ahmed, 2011(Ahmed, , 2013(Ahmed, , 2014b(Ahmed, , 2016Ahmed and Wieraszko, 2012;Samaddar et al, 2017).…”
Section: Tsdcs Mechanisms Of Action and Safetymentioning
confidence: 99%
“…Hence, a given electrical field polarity can increase spinal tract excitability in the white matter and simultaneously decrease excitability in neural elements in the gray matter, or vice versa. There is some pioneering work exploring the effects of tsDCS in animals (Fuortes, 1954), showing the potential of this technique in modulating spinal circuitry (Ahmed, 2011(Ahmed, , 2013(Ahmed, , 2014b(Ahmed, , 2016Ahmed and Wieraszko, 2012;Samaddar et al, 2017).…”
Section: Tsdcs Mechanisms Of Action and Safetymentioning
confidence: 99%
“…Finally, a novel and exciting mechanism of action has been recently proposed by Samaddar and co-workers [353]: they found that tsDCS also modulates the migration and proliferation of adult newly born spinal cells in mice, a cell population implicated in learning and memory; although the mechanisms are not fully understood, these findings suggest that tsDCS could be used, also in humans, as an early treatment to improve motor recovery in spinal cord lesions. In this connection, another study has confirmed that tsDCS increases locomotor skill acquisition and retention in healthy volunteers [354].…”
Section: Tsdcs On Clinical Applicationsmentioning
confidence: 99%
“…It has been proposed that tsDCS can cause long‐term changes in the excitability of spinal cord circuits (Bolzoni & Jankowska, ; Samaddar et al . ; Song et al . ; Wieraszko & Ahmed, ; Ahmed, , ).…”
Section: Introductionmentioning
confidence: 99%